Correlation between erythrocyte aldose reductase level and human diabetic retinopathy. Issue 12 (1st December 2002) - Oishi, N; Kubo, E; Takamura, Y; Maekawa, K; Tanimoto, T; Akagi, Y
Abstract : Aim: To examine the relation between aldose reductase (AR) and the development and progression of diabetic retinopathy by comparing the erythrocyte AR levels with the prevalence of diabetic retinopathy in NIDDM patients. Methods: A clinic based cross sectional study was used. 611 NIDDM patients and 73 controls were enrolled. Erythrocyte AR levels were determined by ELISA. These AR levels were then correlated with patient age, duration of diabetes, and HbA1c levels. AR levels were also correlated with the prevalence of diabetic retinopathy in the entire NIDDM patient group and in three subgroups formed by separating the NIDDM patients by their duration of diabetes. The prevalence of diabetic retinopathy significantly increased with increased erythrocyte AR levels in patients with duration of diabetes of less than 10 years. A similar, but non-significant correlation between the prevalence of retinopathy and increased erythrocyte AR levels was observed in patients with diabetes duration of 10–20 and ≥20 years. Results: The prevalence of diabetic retinopathy increased with increased erythrocyte AR levels in NIDDM patients with a duration of diabetes of less than 10 years. Conclusion: It was suggested that the inhibition of AR in patients with early NIDDM might be beneficial in reducing the development of diabetic retinopathy.